Comparative Effectiveness of After-School Programs to Increase Physical Activity. (4th August 2013) - Gesell, Sabina B.; Sommer, Evan C.; Lambert, E. Warren; Vides de Andrade, Ana Regina; Whitaker, Lauren; Davis, Lauren; Beech, Bettina M.; Mitchell, Stephanie J.; Arinze, Nkiruka; Neloms, Stevon; Ryan, Colleen K.; Barkin, Shari L.
Abstract : Background . We conducted a comparative effectiveness analysis to evaluate the difference in the amount of physical activity children engaged in when enrolled in a physical activity-enhanced after-school program based in a community recreation center versus a standard school-based after-school program. Methods . The study was a natural experiment with 54 elementary school children attending the community ASP and 37 attending the school-based ASP. Accelerometry was used to measure physical activity. Data were collected at baseline, 6 weeks, and 12 weeks, with 91% retention. Results . At baseline, 43% of the multiethnic sample was overweight/obese, and the mean age was 7.9 years (SD = 1.7). Linear latent growth models suggested that the average difference between the two groups of children at Week 12 was 14.7 percentage points in moderate-vigorous physical activity (P < . 001 ). Cost analysis suggested that children attending traditional school-based ASPs—at an average cost of 17.67 per day—would need an additional daily investment of 1.59 per child for 12 weeks to increase their moderate-vigorous physical activity by a model-implied 14.7 percentage points. Conclusions . A low-cost, alternative after-school program featuring adult-led physical activities in a community recreation center was associated with increased physical activity compared to standard-of-care school-based after-school program.